Ontology, Epistemology, and Axiology of Islamic Philosophy - Nurhayani Syafitri; Didik Himmawan; Reny Anggraeni (Konsultan Jurnal Ilmiah Indonesia, 2024)
The systematics of philosophy in general there are three main discussions or parts, namely; epistemology or theory of knowledge that discusses how we gain knowledge, ontology or theory of nature that discusses the nature of everything that gives birth to knowledge and axiology or theory of value that discusses the use of knowledge. philosophy of Islamic education is essentially the concept of thinking about education that is sourced or based on Islamic teachings about the nature of human abilities. The writing of this article discusses the philosophy of ontology, epistemology, and axiology by using literature studies or research from various scientific papers and books related to the topic. The analysis states that ontology basically talks about the nature. the aim is to prove and examine the truth. Epistemology discusses the basis, source, characteristics, truth, and how knowledge is obtained. Epistemology promotes science. It focuses on how scientists use sources and methods to develop knowledge. Each field of science has its own characteristics, and scientists utilize objects, statements, propositions, and characteristics as key components in the development of the understanding gained from this research. It focuses on three philosophical foundations, namely epistemology, axiology, and ontology. Its relation to education is that ontology, epistemology and axiology examine the existence of a science, how to obtain knowledge and how to utilize the knowledge mastered.